Report of the Trade and Commerce Committee of the Loyal National Repeal Association on the hosiery trade. Read at meeting of the association, on [...] May 5th, 1845. [By E. Brodrick] (Browne])
In: First general report of the Trade and Commerce Committee, of the Loyal National Repeal Association.